WAYS TO IMPROVE THE ENTERPRISE’S CAPITAL ACCOUNT - Aimagambetova Aida; Oralbayeva Aizhan; Akhmetova Aigul; Ospanova Gulpat (Academic Journal of Physical and Chemical Sciences, 2020)
Equity capital of any business entity is one of the types of economic capital category. It is essential for the proper functioning of the institution due to changes in the sources of formation and environment. Capital contributed by the founders at the opening of the company, is considered to be the initial funds used to organize the initial activity of the enterprise, or additional funds in a period of growth and expansion. In addition, equity capital protects institutions from financial instability and excessive risks, protects them from bankruptcy, covers losses of current expenses, increases customer confidence, and meets the needs of the clientele in commercial and consumer goods. To ensure the life of the enterprise in modern conditions, management personnel must, first of all, clearly assess the financial condition of their enterprise and potential competitors. Financial position is the most important characteristic of an enterprise’s economic activity. It assesses the competitiveness, potential of business cooperation, and the extent to which the economic interests of the company and its partners in financial and industrial relations are secured. However, the ability to determine the real financial situation is not sufficient for the successful operation of the enterprise and the achievement of its goals. The company organizes accounting depending on its actual state, volume and type of activity: independently determines the forms of organization of accounting work; forms accounting policies; determines the scope of financial and industrial accounting; develops the procedure for monitoring economic operations, as well as makes other necessary decisions for the organization of accounting. In addition, you can see that the company has recently been developing dynamically and is a profitable enterprise. Other important indicators show high performance and development directions. In General, this company is one of the most promising and large taxpayers. Therefore, the analysis of the main indicators that characterize the effectiveness of the enterprise in the conditions of market relations is carried out. The ability to calculate them correctly, identify the impact of various causes on changes in their level, analysis allows you to more widely disclose reserves for improving production efficiency, develop proposals to eliminate the identified shortcomings, improve the financial situation and develop. It is necessary to take into account the achievements of the development of economic activities of the organization. The process of formation of the volume and structure of the capital of the organization should be organized not only at the beginning of its economic activity, but also in order to continue and increase future activities. And its achievements are determined by the capital structure and business plan.